Yildiz Sistemlerinde Elementlerin Oluşumu - Durası, Cihan (Fen Bilimleri Enstitüsü, 1998)
Evrende var olan tüm elementlerin bolluğunun, Büyük Patlamadan (Big Bang) günümüze kadar çeşitli nükleer reaksiyonların sentezleri sonucu bugünkü oranlarına ulaştıkları sanılmaktadır. Bilindiği gibi, nükleer reaksiyonlarla element üretimi, yıldızlarda doğum zamanlarından itibaren başlayıp evrimlerinin son noktasına kadar devam etmektedir. Aynı zamanda yıldızlar arası ortamda var olan gaz ve toz bulutları, kozmik ışınlar tarafından bombardıman edilerek, element sentezine katkıda bulunurlar. Yıldızların merkezlerinde nükleer reaksiyonların mevcudiyeti, yıldızların evrimleri boyunca yayınladıkları enerji kaynağını açıklama konusunda başarılı olmuş ise de, geliştirilen yıldız modelleri, evrende gözlenen element bolluklarını açıklayamamaktadır. Örneğin güneş sisteminde ve diğer yıldız yüzeylerinde gözlenen Mg, Mg, Si", Si ve daha bir çok izotop hidreostatik denge halindeki yıldızlarda meydana gelmezler. Yine, D, Li, Be, B gibi hafif elementlerin gözlenen bollukları, öne sürülen teorilerle ve modellerle uyuşmamaktadır. Çünkü bu hafif elementler, kabul gören yıldız modellerinde üretilmeyip, sadece kullanılırlar, fakat yapılan gözlemlerde bu hafif elementlerin bolluk oranlan yüksek çıkmaktadır. Aynı şekilde He çekirdeğinin gözlenen ve yıldız modellerinden elde edilen oranlan da birbirleriyle uyuşmamaktadır. Bu uyuşmazlığı ortadan kaldırmak için hafif elementlerin yıldızlar arası ortamda kozmik ışınlarla da üretildikleri varsayılmaktadır. He, D ve 7Li gibi hafif çekirdeklerin de Büyük Patlama sonrası ilkel evren döneminde oluştukları fikri ortaya atılmıştır. Bu tez çalışmasında temel amaç, KOCABAŞ ve LANGLEY (1998) tarafından geliştirilmiş olan ASTRA programının ürettiği reaksiyon zincirleri yardımıyla bu güne kadar kabul gören reaksiyon zincirlerine alternatif reaksiyonlar geliştirerek, bahsi geçen uyuşmazlık noktalarına bir yorum getirmekti. ASTRA programı H 'den başlayıp O1 kadar olasılığı mümkün tüm ekzotermik füzyon ve bozunma reaksiyonlarını, ve istenen elemente giden mümkün bütün reaksiyon zincirlerini vermektedir. Yukarıdaki amaca uygun olarak bu çalışmada sırasıyla, elementlerin üretildiği yıldız sistemlerinin, yıldızlar arası gaz ve toz bulutundan, hangi şartlarda meydana geldikleri, Hayashi'nin yaklaşımıyla incelendi. Yıldız, kendisini meydana getiren gaz ve toz bulutunun kimyasal yapısına ve ilkel kütlesine bağlı olarak, farklı evrim yollan izleyebilir. Bu farklılıklar dikkate alınarak, H-R diyagramında, yıldızların izleyebilecekleri evrim yollan üzerinde duruldu. Yıldızlara evrim süreçleri boyunca, kütle ve kimyasal yapılarına bağlı olarak, merkezlerinde ağır elementleri, hangi süreçlerde ürettiklerine, mevcut teoriler ışığında bakıldı. Tartışma kısmında ise ASTRA programının verilerinden yola çıkarak alternatif reaksiyonlar önerildi.

In this thesis, the main subject of research is the nucleosynthesis of light chemical elements. Before discussing the issues of nucleosynthesis, a summary of current information about the classification and evolution of stars is given. Then, the energy resources of stars are discussed. This is followed by a summary discussion on the formation of chemical elements from hydrogen and helium. Finally, current and hypotheses and explanations about the reaction mechanisms for the nucleosynthesis of elements from helium to oxygen, are reviewed in the light of the results of a program, ASTRA developed by KOCABAŞ and LANGLEY (1998), which generates all possible reactions of the light elements, and the reaction mechanisms that lead to their synthesis. Stellar Evolution Stars are formed out of the intersteller matter. The stellar formation is believed to take place preferably in the galactic arms, where the intestellar matter is compresssed. If the radius of a spherical mass of gas is forced to decrease under a critical value computed by Jeans, it becomes unstable, and collapses and leads to a protostar. When the radius of the protostar is not too large (R=105 Re), the collapse is rather rapid (-500 yr) and the protostar becomes very luminous. Then the pressure forces inside the protostar begin to brake the gravitational collapse. The star goes on contracting in a thermostatic time (107 yr). After this phase the protostar becomes very luminous, and because of the collapse, the gravitional force change to kinetic and heat energy. Then, the temperature and the density at the center of the star becomes high enough for H nuclear burning to take place. During the H nuclear burning, protostar stops to collapse, because the pressure forces are larger than gravitational forces. In this way, the star takes its particular place as a main-sequence star in the Hertzsprung-Russell diagram, depending on its mass. Main-Sequence Phase A star in the main-sequence burns hydrogen in its core, and radiates energy, and this goes on as long as the star is in this phase. In order to maintain its thermal equilibrium, the star's energy production and energy loss must be balanced. A star with the size of the sun, the period spent in the main-sequence is about 1010 years. The most important parameter in the study of stellar evolution is the mass. Stars which are more massive then the sun, leave the main-sequence faster. Red Giant Phase When about %10 of the H has been transformed into He, the nuclear energy is no more sufficient to compensate the energy losses. In a short period, the whole star begins to collapse, the layers above the He-rich core burns H. When the temperature is high enough for H to burn outside the core, the outer zones expand while the core goes on contracting. The stellar radius increases, the external temperature decreases due to the expansion, and the luminosity decreases very slowly according to the mass-luminosity relation. The representative point in the H-R diagram stops when the central temperature becomes high enough for He to burn into C and O, and so the star becomes a red giant. Later, at about 8xl08 K, carbon starts burning, and at 109 K, oxygen burning begins to take place. If the core contraction increases the temperature to about 4-5x1 09 K, then Si-burning reactions occur. Si is one of the stable elements, and transforms into Fe group of elements in further fusion processes. In the red giant stage, the He burning quicker than the H burning that take place in the main sequence. This is due to the fact that each He burning reaction releases less energy than H burning reactions. Stars with larger mass have higher core temperatures, they emit more radiation and their masses are converted into energy faster. After this point, the future life of the star is determined by its mass. If the mass of the star is not sufficiently large, carbon, the product of He-burning, cannot be burned by the star. In their last stage, such stars lose their outer layers, but the center goes on to contract, until the electron pressure balances contraction, and the star completes its evolution as a white dwarf. In the case of the stars with sufficient mass, the core collapses rapidly, and as a result of this collapse, the outer layers explode. Then the star becomes a supernove with a luminosity 109 times than that of a normal star. Final Stages of Stellar Evolution The final phases of the evolution of stars depend on the mass. From their birth, stars produce chemical elements as a result of a series of reactions. Depending on the mass, and chemical composition of its core, the elements in the core are transformed into higher elements, and this process ends with the production of iron. As iron has the highest binding energy per nucleon among all other elements, it would not transform into other elements by further fusion and fission reactions. When the star's core is transformed into iron, it would start to collapse, as there would be no source of outward heat and pressure. From this point onwards, the star completes its evolution in one of the three ways. When the mass M < 1.44 Mo, the possible stable state for the star is to become a white dwarf. The diameter of a white dwarf is about 3000 km. The surface temperature of such stars is between l-2xl04 K. As their surface area is small, their XI luminosity is low. For this reason, they are observed as faint blue stars. These stars lose their energy only by radiation, and as a result, their cooling period is long. When the mass is 1.44 M© < M <- 5:6 M©, the star can turn into a neutron star. Neutron stars are highly dense stars, and their density at the core can be 1016 gr/cm3, and their diameter is about 10 Km. When the mass M > 5.6 Mq, there would be nothing to prevent the gravitational collapse, and the star ends its evolution as a black hole. Gravitational diameter is Rg = 2GM/c2, no light can escape from within the star, and for this reason black holes cannot be observed optically. Energy Sources of Stars At their early stage, stars gain their energy from gravitational contraction until they reach the main sequence stage. In the main sequence their energy source is nuclear reactions. During the formation of the stars, the temperature at the core increases, and the nuclear reactions start at the core. There are two types of nuclear reaction, exothermic and endothermic. The types reactions that take place in a star depends on the chemical composition, the temperature, and the density of the star. The main types of exothermic reaction that can take place in stars are H-burning and He-burning (BETHE,1938 ; von WEIZSACKER, 1937 ). Hydrogen Burning Reactions; Hydrogen burning processes take place by the transformation of hydrogen atoms into helium. There are three known H-burning reaction mechanisms in stars with masses 1.5-2 Me. These are called as PPI, PPII and PPin chains. In stars with larger masses, there are other mechanisms, the CNO chains, that burn hyrogen. Helium Burning; Helium burning essentially consists of the fusion of three helium atoms to form a carbon atom ( FOWLER, 1986 ). Comparing the energy production per nucleon in hydrogen fusion to that in helium fusion, we find that hydrogen fusion produces 10 times more energy per nucleon than does helium fusion. When the mass fraction of carbon inreases in the center of the star then carbon atoms interact with helium to form an oxygen atom and the oxygen interacts with another helium to form Ne, and so on. In principle, the nucleosynthesis might proceed further, up to the formation of iron. So the exothermic reactions stop at the iron-group nuclei, but higher elements can be built up by some other reactions utilising the particles' thermal energies. The most important groups of these reactions are s and r processes. The s process occurs at the low temperatures, somewhat over 108 K. It is the capture of neutrons by nuclei at a rate slower than the radioactive decay times of the products. The s process is thought to uccur after the ignition of helium layers. Xll The s process cannot make nuclei beyond A= 209, because further neutron capture produces nuclei in the region of the periodic table where a decay is fast and returns nuclei to A= 209 or below (WILLIAMS, 1991, p. 355). The r-proccess requires temperatures over 1010 K. It is related to the s process and is just neutron capture at a rate which is more rapid than the products' decay times. It requires a very high neutron flux and is thought to occur for a few seconds during supernova explosions. Although the reaction mechanisms proposed explain the synthesis of chemical elements in stellar and interstellar medium, the abundances of the elements in the universe is still not well undestood. The anomalies in the aboundances of the elements in the solar system suggests that they were formed as a result of different fusion processes. Although the nuclear reaction explain the evolution of stars from birth to their death, they fail to explain the observed abundances of elements in the universe. In the proposed mechanisms for hyrogen burning, the light elements (D, Li, Be, and B), are not formed, but destroyed by nuclear reactions in stars. The abundances of He and the other light elements are found in observations higher than expected. It is assumed that these elements were formed during the Big Bang. The existence and the abundances of heavier isotopes Mg, Mg, Si, and Si and many others cannot be formed by hydrostatically stable stars (AUDOUZE and VAUCLAIR, 1980, p.58). Although the stellar models that have been proposed to date explain many events in stars, they remain to be insufficient in explaining all possible nucleosyntheses. In this situation, it seems to be necessary to consider all possible reaction mechanisms, to explain the unexplained observations. The ASTRA program developed by KOCABAŞ and LANGLEY (1998) provides an opportunity for a new way of looking at the stellar nucleosyntheses, as this system generates all possible exothermic nuclear reactions of the light elements from H to O16. Based on the output of this program, it seems possible to identify alternative reaction chains that would explain the anomalies between the current explanations and observations. The ASTRA program produces all exothermic reactions, as stated above, and predicts that all elements from hydrogen to nitrogen (N15), with the exception of He4, participate in proton capture. The program produces 46 such reactions, including all the 33 examples which were examined by astrophysicists, with the 13 other reactions which do not appear in the texts: Some of these are: X1U In fusion reactions that involve neutron capture, an element combines with a neutron to form a heavier isotope of the same element. ASTRA produces 59 such reactions, while only 17 neutron capture reactions appear in the literature. Some of the reactions which we did not see in the texts are: Be7 He4 Be9 B11 016 + + + He4 6.47 MeV 18.97 MeV 1.67 MeV 11.37 MeV 12.91 MeV Neutron capture requires a continuous supply of neutrons in the stellar plasma, so that it relies on some neutron-producing reaction. AUDOUZE and VAUCLADR (1980, p.86) suggest that D + D Hej + n which combines two deuterons, is the only reaction that releases neutrons in the hydrogen-burning stage of main-sequence stars. Yet ASTRA also predicts six additional reactions that produce neutrons: D D He3 D He4 D + + + + + + Li6 Li7 Be9 Be9 B11 17.03 MeV 3.33 MeV 9.33 MeV 4.23 MeV 5.63 MeV 13.63 MeV The second reaction seems especially important, as both D and Li6 are stable and exist in the main sequence stars, and thus could play a role in stellar reaction path ways. Many of the neutron-producing reactions rely on a deuteron as one of their inputs. The best known deuteron-generating reaction is H + H - > D + e" + v, and there are two other reactions which are appear in astrophysics texts. T H + + He3 Be9 He4 Be8 + + D D But the ASTRA program gives 15 other reactions that also produce D: XIV 0.30 MeV 11.90 MeV 1.40 MeV 10.60 MeV 2.16 MeV The first two of these reactions are possible in main-sequence stars, as Li and Li are known to exist there. Astrophysicists assume that hydrogen-burning is the principal energy source in main- sequence, where H transforms in to He4 ( WILLIAMS, 1991, p. 351). When asked to generate reaction pathways from H to He, the ASTRA system finds all the known reaction pathways. The program also finds some 44 other process accounts of helium generation. For example these include the two reaction pathways: and 4H ? He4 + e +. e + v + v CUJEC and FOWLER (1980) and HARRIS, FOWLER, CAUGHLAN, and ZIMMERMAN (1983) argue that reactions involving D are unlikely due to its relatively low abundance. However, CLAYTON (1983, pp.371-2) notes that the density of deuterium in the interstellar medium and the sun remains unknown, and suggests that the substance might be more common than usually believed. From this perspective, the above reaction pathways provide plausible novel accounts of helium production. To explain the synthesis of carbon and oxygen from helium, as we have noted above, the reaction chain proposed by astrophysicists consists of the fusion of three helium atoms to form a carbon atom. FOWLER (1986, pp. 5-6) proposes the pathway as below: - ? Be8 c12 016 But the first reaction above is endothermic and the lifetime of Be8 is very short (2x1 0"16 sec). ASTRA finds 20 other reactions that produce, Be8 such as: XV D + Li6 ? Be8 + Li7 ? Be8 + Be7 ? Be8 He3 + Li7 ? Be0 + D n The system produces also 24 additional pathways that differ in their final steps to C12, some of them are given below: C12 26.20 MeV C12 + H 19.62 MeV C12 7.30 MeV C12 + n 5.63 MeV 1İ2 j_ tt~4 -? C" + He* 13.46 MeV which contribute to a total of 8.2x1 014 more pathways for C12 synthesis than astrophysicists appear to have entertained. These include: + n 8 which relies on one of the neutron-capture reactions we discussed earlier. If Be captures a neutron before it decays, then it transforms into its stable isotope. This in turn produces carbon by reacting with He4, where the emitted neutron from the latter reaction can combine with another Be8. The two other novel pathways are: He4 + D ? Li6 He3 + Li6 ? Be9 He4 + Be9 > C12 + n and He4 + D ? Li6 He4 + Li6 ? B10 He4 + B10 ? C12 + D 3He4 where the net effect is 3He4 --> C12. When enough C12 produced, then it can react with helium to form O16, as stated in existing literature: XVI He4 +,12 O 16 But ASTRA finds other reaction pathtways to oxygen such as, and He4 He3 He4 He3 He4 He4 He4 He3 + + + + + + + + D Li6 Be9 ^13 D Li6 B1( N1' Lib Be9 /-.13 O 16 Li6 B1 N O + H In summary, ASTRA finds a number of reaction pathways to carbon and oxyden that physicists appear to have missed, just as they have done in the case of the lighter element helium. All of these pathways are theoretically possible, but final judgement about their scientific value requeres further evaluation.
Nucleosynthesıs Of Chemıcal Elements In Stars
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Nükleer reaksiyonlar; Yıldızlar; Nuclear reactions; Stars